Spray processing of TiO2 nanoparticle/ionomer coatings on carbon nanotube scaffolds for solid-state supercapacitors - Huang, C; Young, N; Grant, P (Royal Society of Chemistry, 2014)
A one-step scalable spray technique was used to fabricate solid-state supercapacitors with multi-wall carbon nanotube/TiO2-nanoparticle/ ionomer hybrid electrodes. The 3D electrode nanostructure was designed for mobile H+ ion generation and fast electron-ion dual conduction, achieving an unusual and highly attractive balance of energy (31.8 W h kg -1) and power (14.9 kW kg-1) densities at 1 A g -1 that are amongst highest reported for solid-state supercapacitors. © 2014 the Partner Organisations.